Conselhos tutelares (ou tutelados?): a experiência no município de Goiânia, 1993 a 2008 - Queiroz, Lúcia Abadia de Carvalho (2009)
This work sets up a general characterization of the Guardianship Councils (CTS) in Goiânia-GO and it investigates the actions of such boards. This study chose as the empirical unit CTS, by understanding them as legitimate bodies responsible for care of the rights of children and adolescents in the municipality. The goal is to delineate the professional and socio-economical profile and to exam the internal dynamics provided by CTS. It identifies the operation, expertise, political legitimacy and greater incidence of the demands made in a context of denial of social rights and continued violation of the rights of children and adolescents. It takes into account that the CTS have the precepts of the Statute of Children and Adolescents (ACE), the guiding principle of his actions and that the creation of the CTS is scheduled in its title V, 131. The ECA is understood as the result of collective struggle of mobilized sectors of civil society (National Movement of Street Boys and Girls, National Movement for Human Rights and others), in defending the rights of children and adolescents, as part of a broad process of efforts, actions and disputes in the construction of democracy and extended citizenship. The survey conducted revealed that, despite the advances and achievements, some of CTS in Goiânia-GO are away from ethical and political commitment as guardians of the rights of the segments at risk and social vulnerability. It is understood that this condition results from a vulnerable inhuman and unequal concentration of wealth that exposes, weakens and penalizes hundreds of families of low purchasing power which, by the situation of poverty (extreme or relative), have no power to enforce the vocalization of their rights before the authorities. Such Councils, however, are in continuous danger of being protected by the municipal executive, which in turn is assumed as a priority the zeal for the rights of children and adolescents in the municipality. These processes have produced a great gap in the field of rights, especially between what is legal (rights guaranteed by law) and situation (right denied) in Goiânia. Finally, having as the horizon the consolidation of citizenship rights of these segments, it is understood as one of the challenges that civil society must mobilize itself to ensure effectiveness of the mechanisms of democratic control, including the performance of CTS. It is expected that civil society strengthen the CTS, in the light of the principles of the ECA, including them as instances of building participatory democracy.